ON THE GEOCHEMISTRY OF TA, NB, ZR, AND HF IN F-ENRICHED GRANITES AND ALKALINE ROCKS: EXPERIMENTAL DATA - Gramenitskiy E.N.; Shchekina T.I. (My University, 2001)
According to experimental data on granitic and nepheline syenitic systems, Ta, Nh, Zr, and Hf in equilibrium aluminosilicate acid aluminofluoride melts are preferably concentrated in the Former. Crystallization differentiation is proved to play the leading role in the enrichment of these elements during the magmatic process, with the enrichment process enhanced by the segregation of the aluminofluoride melt. The partition coefficients of these elements notably decrease when Li is added to the system, with this effect pronounced most strongly for Zr and Hf (the partition coefficient of Hf approaches unity). In addition to Li, the partition coefficients of these elements are also affected by the K/Na ratio of the system, its silica content, agpaitic coefficient, and the partial replacement of F by CO2. The variation tendencies are different (up to the opposite ones) for chemically similar elements, because of which their ratios (geochemical indicators) are also changed. Our experimental results are mostly consistent with and explained the empirical geochemical data.